Some theorems on the convergence of series in Bessel-Maitland functions - Paneva-Konovska, Jordanka (Ann. Sofia Univ. Fac. Math. and Inf., 2009)
Some important properties of the power series in complex domain are given by the classical Cauchy-Hadamard, Abel and Tauber theorems. In this paper we prove same type theorems for series in the Bessel-Maitland functions.